The Influence of Work Discipline, Work Ethics and Work Environment on Employee Performance at the Regional Company Pasar Horas Jaya, Pematangsiantar City - Santi Rohdearni Panjaitan; Diana Florenta Butarbutar; Hadi Panjaitan; Anju Bherna D Nainggolan; Ben Setiawan Barus (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
This study aims to see the effect of work discipline, work ethic and work environment on employee performance, either partially or simultaneously at PD Pasar Horas Jaya, Pematangsiantar City. The type of research used is quantitative. The population in this study were employees of the PD Pasar Horas Jaya office, Pematangsiantar City, amounting to 31 people and the determination of the number of samples in this study was by the sampling method. The data source of this research is primary data by using research instrument in the form of a questionnaire. The data collection method used is survey research. This study uses multiple linear regression analysis for statistical analysis and the regression model has been tested first in the classical assumption test. The results of the study stated that the partial test showed that work discipline had a significant positive effect on employee performance at PD Pasar Horas Jaya Pematangsiantar City, the partial test showed that work ethic had a significant positive effect on employee performance at PD Pasar Horas Jaya Pematangsiantar and partially tested the work environment had a positive effect. significant effect on employee performance at PD Pasar Horas Jaya Pematangsiantar Together, work discipline, work ethic and work environment have a significant effect on employee performance at PD Pasar Horas Jaya Pematangsiantar.